Keterampilan Menyusun Jurnal dalam Siklus Akuntansi dan Kemandirian Belajar melaui Model Project Based Learning (PjBL) dan Inquiry - Juwarni, Juwarni; Mila, Hilyati; Risnanosanti, Risnanosanti (JOEAI (Journal of Education and Instruction), 2026)
This study aims to analyze differences in journaling skills during the accounting cycle and in student learning independence when applying the Project-Based Learning (PjBL) and Inquiry models compared to the conventional model. The method used was a quasi-experimental model with a non-equivalent pre-test and post-test control group design. The results showed significant differences in journaling skills among the three groups (p = 0.005 < 0.05). The Inquiry model (Mean Rank 48.06) and PjBL (Mean Rank 45.24) were significantly more effective than the conventional model (Mean Rank 29.18). For the learning independence variable, the PjBL model (Mean Rank 54.02) proved significantly superior to the Inquiry (34.54) and conventional (32.79) models. In conclusion, the PjBL and Inquiry models are effective in improving students' technical accounting skills due to their student-centered nature. However, the PjBL model has a stronger impact on developing independent learning through autonomy in real-life project work.   Keywords: Inquiry, Accounting Journal, Learning Independence, PjBL